Diagnosis and symptoms of mental health disorders in adolescents after the Covid-19 pandemic in a middle-income country: a cross-sectional study (Brazilian Journal of Health Research, 2026)
Introduction: The early periods of the COVID-19 pandemic showed worrying mental health trends in multiple populations. Adolescents from low- and middle-income countries may have been disproportionately affected with mental disorders. Objectives: to describe the characteristics of adolescents, who returned to a public school after COVID-19, and the factors associated with symptoms of mental disorders in a middle-income country. Methods: A cross‐sectional study was conducted with adolescents, who returned to school after the pandemic. Personal characteristics, diagnosis of mental disorder, and symptoms of mental disorders were collected by questionnaires, between May 2022 and December 2022. Pearson correlation coefficients or Chi-Square tests were used to explore the relationships between personal factors and suspicious mental disorders. Results: Among 365 potential participants, 145 adolescents (72 girls) agreed to answer the questionnaires. Included adolescents had a mean age of 13 years (SD 1). The percentage of adolescents, who were diagnosed with mental disorders after the COVID-19 pandemic increased by 12%. Over 50% of the adolescents reported symptoms of mental disorders. Sex (r = 0.49; p < 0.01), and previous COVID-19 contamination (r = 0.18; p = 0.03) were associated with suspicious mental disorders. Conclusions: The findings suggest that diagnosis and symptoms of mental disorders increased in adolescents after the COVID-19 pandemic. Sex and previous COVID-19 contamination were associated with suspicious mental disorders. Monitoring of adolescents after the COVID-19 pandemic in low- and middle-income countries is strongly recommended.
Keywords: Adolescent; Anxiety; Depression; Social Participation; Observational Study